An analisis of the CO2 emission abatement in plastic recycling system using life cycle assessment (LCA) methodology: a case study of Bandung city, Indonesia - , Hendrawan; Dowaki, Kiyosho; Putro, Utomo Sarjono (SBM ITB, 2010)
Global warming issue becomes a main issue in sustainable development planning for every country in the world. Indonesia as developing country has commitment to contribute in CO2 abatement with proper development policies. Since May 2008 Indonesia has introduced new law of Solid Waste Management (UU No. 18/2008), the basis of waste management under this law is waste reduction to a landfill as the first priority. The highest waste material compositions in general are organic (50%) and plastic (15%) such as PET, PP, etc. In Indonesia, plastic is common to use as container/packaging. Plastic in Indonesia still using petroleum-based container/packaging and it contributes CO2 emission in the life cycle. Thus, the recycling system on the plastic is significant in order to mitigate CO2 emissions. That is, in this paper, we find the optimal system so as to reduce CO2 emission in the plastic recycling system. The new scenarios on the recycling plastic in transportation sector and manufacturing sector will introduce in this study. In transportation sector, higher truck capacity will introduce to see the effect on CO2 emissions abatement. In manufacturing sector, environmental friendly energy from new renewable energy will introduce to replace conventional energy sector. System Blue Tower (BT) technology through which the environmentally friendly electricity is supplied from municipal organic waste was argued. The proposal of a concrete system would be a CDM (Clean Development Mechanism) project in the near future. This study will model plastic recycling life cycle in Bandung City as a case study.Keywords: Plastic Recycling, LCA, CO abatement, Bandung Cit